Examining perinatal subdural haematoma as an aetiology of extra‐axial hygroma and chronic subdural haematoma. (13th November 2019) - Zahl, Sverre Morten; Wester, Knut; Gabaeff, Steven
Abstract: Aim: Benign external hydrocephalus (BEH), hygroma and chronic subdural haematoma are extra‐axial fluid collections in infants. MRI studies have shown that almost half of all new‐borns have perinatal subdural blood, generally referred to as subdural haematoma (SDH) or perinatal SDH. Epidemiologically there are striking similarities between chronic SDH and BEH in infants. Methods: Discussion of pathophysiological mechanisms for BEH and chronic SDH, based on existing literature. Results: Perinatal SDH is common, and we hypothesise that this condition in some infants develop into extra‐axial fluid collections, known as hygroma, BEH or chronic subdural haematoma. The mechanism seems to be an intradural bleeding that creates an obstructive layer preventing normal CSF absorption. The site where the bleeding originates from and those areas enveloped in blood from the primary damaged area are prone to later rebleeds, seen as 'acute on chronic' haematomas. With steady production of CSF and the blockage, increased intracranial pressure drives the accelerated skull growth seen in many of these children. Conclusion: Perinatal SDH hampers CSF absorption, possibly leading to BEH and chronic SDH, with a high risk of false accusations of abuse. Close monitoring of head circumference could prove vital in detecting children with this condition.